The Effect of Pressure and Temperature on The Particle Board Manufacture from Palm Oil Empty Bunches and Pine Bark - Asfarizal Saad; Anwar Kasim; Gunawarman Gunawarman; Santosa Santosa (Jurnal Teknik Mesin (JTM), 2019)
The manufacture of particle boards without synthetic adhesives is influenced by the composition of the material, temperature, time, pressure, particle size and method of manufacture. The pressure of one important parameter and its variations often produce different properties. Pine skin is a waste that is not valuable and just wasted. Making particle boards from palm oil empty bunches and pine bark waste is an interesting and new thing. Pinus merkusii leather powder is used as an added ingredient, its composition is 70% tkks and 30% pine merkusii powder with 5-6% moisture content, dry based. The fiber lengths are 0.1-2.0 cm and pressures are 2, 4, 6, 8 and 10 kg.cm-2, temperature 150, 160, 170, 180 and 190ºC. The standard for particle board reference and bending test is SNI 03-2105-2006 and ASTM D1037. The result show of working pressure and heating temperature affect the density, moisture content and MOR. Increasing pressure and temperature tend to increase the MOR value and increase in temperature above 190oC, the MOR value decreases.